Performance Evaluation of Bio-Medical Waste Incinerated Ash and Cement Blend as Stabilizing Agent for Low Volume Road Bases - Ramulu Gugulothu; Shankar Sabavath (Journal of Rehabilitation in Civil Engineering)
Incineration is the most commonly employed alternate disposal strategy of biomedical waste across the globe, which produces Biomedical Waste Incinerated Fly Ash (BMWIFA). BMWIFA is often disposed of in landfills to prevent environmental contamination. Due to limited space and the high cost of land disposal, recycling methods and ash reuse in various systems have been developed. Therefore, the present study evaluates the performance of BMWIFA and Ordinary Portland Cement (OPC) blends as stabilizing agents for the base layers of low-volume roads (LVRs). Different trial mixes of crushed aggregate (CA), BMWIFA, and OPC were tested to find the optimum mix. The stabilizer content was considered to be 3.0%, 5.0%, and 7.0% of the total dry weight of the mix, in which the BMWIFA (a)/OPC (c) ratio is taken as 100/0, 80/20, 60/40, 40/60, 20/80, and 0/100 in each percentage of stabilizer. Optimum values of compaction characteristics were used for strength evaluations of mixes in terms of unconfined compressive strength (UCS) and indirect tensile strength (ITS) at 7, 14, and 28 days of air curing. The mix proportions 97% CA, 95% CA, and 93% CA stabilized with 3% (a/c = 20/80), 5% (a/c = 40/60), 7% (a/c = 60/40) binders respectively, satisfied the 7-day UCS requirements (3MPa) according to the Ministry of Rural Development (MoRD) for LVR cement-treated bases and were found durable. Furthermore, the Toxicity Characteristics Leaching Procedure (TCLP) analysis for various heavy metals reveals that the CA, BMWIFA, and OPC compositions were non-hazardous materials. Finally, this study's findings recommend the use of BMWIFA and OPC blends as stabilizers in low-volume road construction.